The Supernaturalist - Colfer, Eoin (Hyperion, 2004)
In futuristic Satellite City, fourteen-year-old Cosmo Hill escapes from his abusive orphanage and teams up with three other people who share his unusual ability to see supernatural creatures, and together they determine the nature and purpose of the swarming blue Parasites that are invisible to most humans.